德国标准的平键计算方法简介 - 李丹凤; 张耀周 (Jixie chuandong)
The parallel keys calculation method of DIN is introduced and some factors are listed.A example is calculated by the two different method of mechanical design handbook and DIN.But DIN is more particular and tallies with practice.